1999
DOI: 10.1128/mcb.19.9.6065
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of TLC1 (Which Encodes the RNA Subunit of Telomerase), TEL1, and MEC1 in Regulating Telomere Length in the Yeast Saccharomyces cerevisiae

Abstract: In the yeast Saccharomyces cerevisiae, chromosomes terminate with a repetitive sequence [poly(TG 1-3 )] 350 to 500 bp in length. Strains with a mutation of TEL1, a homolog of the human gene (ATM) mutated in patients with ataxia telangiectasia, have short but stable telomeric repeats. Mutations of TLC1 (encoding the RNA subunit of telomerase) result in strains that have continually shortening telomeres and a gradual loss of cell viability; survivors of senescence arise as a consequence of a Rad52p-dependent rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
264
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(286 citation statements)
references
References 46 publications
19
264
2
1
Order By: Relevance
“…The short telomere phenotype is found in both A-T cells that express strong telomerase activity (e.g., the SV40-transformed fibroblasts used for our experiments) and in A-T cells that lack telomerase activity (primary diploid fibroblasts and lymphocytes) (e.g., Xia et al, 1996). This conclusion is further supported by recent findings in S. cerevisiae that indicate that the role of Tel1p in telomere length control is at least partially independent of telomerase function (Ritchie et al, 1999). The telomere lengthening seen in TEL1-transfected A-T cells is also unlikely to be the result of activating the so-called ALT pathway, in that our stably TEL1-transfected A-T cells did not show the extensive heterogeneity and bimodal distribution of telomere length that is characteristic for this mechanism of telomere extension (Murnane et al, 1994;Bryan et al, 1995;Sprung et al, 1997).…”
Section: Tel1 Expression Leads To Telomere Lengthening In A-t Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…The short telomere phenotype is found in both A-T cells that express strong telomerase activity (e.g., the SV40-transformed fibroblasts used for our experiments) and in A-T cells that lack telomerase activity (primary diploid fibroblasts and lymphocytes) (e.g., Xia et al, 1996). This conclusion is further supported by recent findings in S. cerevisiae that indicate that the role of Tel1p in telomere length control is at least partially independent of telomerase function (Ritchie et al, 1999). The telomere lengthening seen in TEL1-transfected A-T cells is also unlikely to be the result of activating the so-called ALT pathway, in that our stably TEL1-transfected A-T cells did not show the extensive heterogeneity and bimodal distribution of telomere length that is characteristic for this mechanism of telomere extension (Murnane et al, 1994;Bryan et al, 1995;Sprung et al, 1997).…”
Section: Tel1 Expression Leads To Telomere Lengthening In A-t Cellssupporting
confidence: 89%
“…Additional support for a functional role of ATM in controlling telomere length is provided by the demonstration that expression of a dominant-negative ATM fragment in normal cells results in a decrease in average telomere repeat length (Smilenov et al, 1997). In yeast, deficiency of the homologous TEL1 gene also leads to gradual telomere shortening (Lustig and Petes, 1986;Greenwell et al, 1995;Ritchie et al, 1999).…”
Section: Tel1 Expression Leads To Telomere Lengthening In A-t Cellsmentioning
confidence: 99%
“…The Cdc13 telomere cap blocks MRX-dependent DNA degradation and in turn decreases Mec1 accumulation at the DNA end, whereas it permits the MRX complex to recruit Tel1 to the DNA end. Although Tel1 plays a minor role in checkpoint response (Morrow et al, 1995;Sanchez et al, 1996), it plays a predominant role in telomere length regulation (Greenwell et al, 1995;Ritchie et al, 1999). Consistently, telomere synthesis from TG 81 ends largely depends on Tel1 (Frank et al, 2006).…”
Section: Checkpoint Inhibition By Telomere Capmentioning
confidence: 95%
“…The maintenance of telomere structure and length is crucial for telomere homeostasis, because dysfunctional or shortened telomeres activate a checkpoint response that is mediated through the ATM and ATR family proteins (d'Adda di Fagagna et al, 2004;de Lange, 2005). However, the ATM and ATR family proteins are also required for proper maintenance of telomeres (Greenwell et al, 1995;Metcalfe et al, 1996;Ritchie et al, 1999). Recent evidence suggests that addition of telomeric TG repeats adjacent to DSBs inhibits the activation of checkpoint response in budding yeast (Michelson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that deletion of either TEL1 (the yeast ATM homolog) or the MRX complex genes RAD50 and MRE11 causes severe telomere shortening (Greenwell et al 1995;Boulton and Jackson 1998), and at least in the case of tel1⌬ a loss of Rap1 counting (Ray and Runge 1999a;Brevet et al 2003). Both Tel1 and MRX are thus thought to be positive regulators of telomerase action, and epistasis analysis would suggest that they act downstream from both RIF1 and RIF2 (Ray and Runge 1999a;Ritchie et al 1999;Ritchie and Petes 2000;Chan et al 2001;Diede and Gottschling 2001;Tsukamoto et al 2001). Significantly, the pol12-216 mutation causes telomere elongation in all three mutant backgrounds (tel1⌬, mre11⌬, and rad50⌬), to slightly longer than wild-type lengths (Fig.…”
Section: Telomere Elongation In Pol12-216 Mutants Requires Telomerasementioning
confidence: 99%